Symposium 1: Theory and the Practices of Learning Technology - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines the link between theory and practice in relation to learning technology. It will do this in the context of a move from working with early adopters to learning technologists engaging with the majority of academic staff (Browne, 2003). This move takes place at the same time that academic staff in tertiary education are being encouraged to engage formally with learning and teaching in a way that is sharply different from previous University practices. Learning technologists currently engage with a broader constituency that is in a significant process of change. The future of networked learning is related to the growth of this emergent profession and the way in which theory relates to their developing practices.